Nonpharmacological Interventions for the Treatment of Cardiometabolic Risk Factors in People With Schizophrenia—A Systematic Review - Tumiel, Ewa; Wichniak, Adam; Jarema, Marek; Lew-Starowicz, Michał (Frontiers in Psychiatry, 2019)
Background. People suffering from schizophrenia are notably vulnerable to cardiometabolic risk factors (CMRF), such as obesity, high blood pressure, hyperglycaemia and insulin resistance, high serum triglycerides and low serum high-density lipoprotein (HDL), that are related to increased mortality and decreased quality of life. The increased risk of “metabolic syndrome” (MS) is related to low physical activity, an unhealthy diet and side effects of antipsychotic drugs. Non-pharmacological interventions seem to be important in the prevention and therapy of MS. Aim. This paper provides an overview of published studies and a critical analysis of pilot programmes involving non-pharmacological measures aimed at prevention and treatment of CMRF in patients with schizophrenia. Material and method. We searched the PubMed, PsycARTICLE, and Cochrane Library databases to identify clinical trials. We included full-text studies that met the following criteria: age>18 years, a diagnosis of schizophrenia or schizoaffective disorder, and monitored parameters associated with MS. Results. All 1555 references were evaluated for inclusion in the review and 20 met the inclusion criteria. Non-pharmacological interventions led to improvement in physical health and showed a promising potential for implementation in treatment programs dedicated to this particular group of patients. However, a critical analysis revealed limitations, which have implications for the direction of future research. Conclusions. Patients suffering from schizophrenia can benefit from non-pharmacological interventions aimed at counteracting CMRF, improving either metabolic parameters, cardiovascular fitness or their health perception. Notwithstanding, in order to achieve long-term effects, future studies should comprise appropriate follow-up procedures.